Immunogenicity and efficacy in hemodialysis patients of an AS03A-adjuvanted vaccine for 2009 pandemic influenza A(H1N1): a nonrandomized trial - Dikow, Ralf; Eckerle, Isabella; Ksoll-Rudek, Dorothea; Hampel, Heidrun; Schwenger, Vedat; Zeier, Martin; Schnitzler, Paul; Sommerer, Claudia (American journal of kidney diseases, 2011)
Background - Hemodialysis patients have a reduced response to vaccinations because of uremia-related immune dysfunction. To increase the immunogenicity of vaccines, antigens can be formulated with adjuvants. The new tocopherol-containing adjuvant system AS03A has not been tested yet in patients with end-stage renal disease. - Study Design - Nonrandomized trial. - Setting & Participants - 291 hemodialysis patients from 3 dialysis units co-operating with the Department of Nephrology at the University Hospital Heidelberg, Germany: 169 patients were vaccinated using either 1 (64 patients) or 2 doses (105 patients); 123 patients refused the vaccination and served as controls. - Intervention - Intramuscular immunization with 3.75 μg of an inactivated split-virion A/California/7/2009 H1N1v pandemic vaccine adjuvanted with AS03A in a single- or double-dose regimen. - Outcomes - A pandemic influenza A immunoglobulin G (IgG) enzyme-linked immunosorbent assay (ELISA) response >11 AU (arbitrary units) was defined as a positive response. - Measurements - Quantitative antibody testing using the pandemic influenza A IgG ELISA. Antibody titers were tested 3 months after vaccination and compared with nonimmunized dialysis patients. - Results - After vaccination against 2009 pandemic influenza A(H1N1), 41 of 64 (64.1%) patients with 1 vaccination and 93 of 105 (88.6%) with 2 vaccinations showed a protective immune response compared with 43 of 123 (34.9%) unvaccinated patients (P < 0.001). Logistic regression analysis confirmed vaccination dose as an independent factor for response to pandemic H1N1 vaccination. No episode of pandemic H1N1 illness occurred in any group within the study period of 6 months after vaccination. No serious adverse events occurred, and local symptoms ranged from mild to moderate in 143 of 169 (84.6%) patients. - Limitations - Nonrandomized assignment; use of nontreated patients as controls; no comparison to nonadjuvanted vaccines; dose variation in the intervention group. - Conclusions - Pandemic H1N1 vaccine adjuvanted with AS03A is immunogenic, effective, and safe in hemodialysis patients.